Development Of Strategic Management Competence Of Managers Of Preschool Education Organizations Based On A Systematic Approach (Eurasian Journal of Learning and Academic Teaching, 2024)
This article highlights the possibilities of a systems approach and, on its basis, the possibility of developing the strategic management competence of managers of preschool educational organizations.